2007
DOI: 10.1111/j.1365-2516.2007.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal bleeding in haemophiliacs: incidence and relation to use of non‐steroidal anti‐inflammatory drugs

Abstract: This multicentre study sought to estimate the incidence of upper gastrointestinal (UGI) bleeding in haemophiliacs and its relationship to use of non-steroidal anti-inflammatory drugs (NSAIDs). Cox models were used to estimate relative hazards (RH) with 95% confidence intervals (CI) for postulated risk factors. Conditional logistic regression and stored sera were used to assess UGI bleeding risk with Heliobacter pylori seropositivity in cases compared with closely matched controls. During a mean of 17.4 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 38 publications
(49 reference statements)
0
32
0
Order By: Relevance
“…35 Upper gastrointestinal bleeding was reported to occur in 42 of 2285 PWHs (incidence, 1.3 per 100 patient-years) and the use of NSAIDs was associated with an increased bleeding risk (hazard ratio ϭ 3.7), whereas the use of COX2 inhibitors was not. 38 Hence, we prefer COX2 inhibitors to NSAIDs when paracetamol, still the drug of first choice, is not effective to control pain. An example of a pain control schedule, based on sequential steps of more and more aggressive treatment in case of failure, is given in Table 3.…”
Section: Pain Controlmentioning
confidence: 99%
“…35 Upper gastrointestinal bleeding was reported to occur in 42 of 2285 PWHs (incidence, 1.3 per 100 patient-years) and the use of NSAIDs was associated with an increased bleeding risk (hazard ratio ϭ 3.7), whereas the use of COX2 inhibitors was not. 38 Hence, we prefer COX2 inhibitors to NSAIDs when paracetamol, still the drug of first choice, is not effective to control pain. An example of a pain control schedule, based on sequential steps of more and more aggressive treatment in case of failure, is given in Table 3.…”
Section: Pain Controlmentioning
confidence: 99%
“…The absolute risk for developing UGI bleeding in a PWH remains unknown. However, in a multicentre study with 2285 patients with haemophilia, there was a 1.3% annual incidence of clinically important UGI bleeding events . This incidence is nearly 10 times greater than the 0.1% UGI bleeding rate reported in those without haemophilia (general population) (Table ).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, it was reported that the RR of GI bleeding was significantly and independently increased with age >46 years (3.5; 95% CI: 1.1–10.6) and hepatic decompensation (4.4; 95% CI: 1.7–11.6). Presence of H. pylori positivity increased the likelihood of UGI bleeding but this did not reach statistical significance (odds ratio: 4.6; 95% CI: 0.3–83.9) . Based on these findings, the authors concluded that COX‐2 inhibitors are safer alternative analgesic and anti‐inflammatory agents for PWH with arthropathy .…”
Section: Introductionmentioning
confidence: 99%
“…29 Managing painful arthropathy with nonaddictive medications is difficult in the older hemophilia patient because of increased risks of nonsteroidal anti-inflammatory agent (NSAID)-associated gastrointestinal bleeding and acetaminophen-associated liver dysfunction. 30,31 In one study, the use of nonselective NSAIDs was associated with an increased likelihood of bleeding, whereas selective COX2 inhibitors were not. 30 The extent of use of long-term continued factor prophylaxis initiated after multiple joint bleeds and established joint damage, so-called "secondary" prophylaxis, in adults over 45 is unknown; its effectiveness in mitigating hemophilic arthropathy is also unknown.…”
Section: Joint Diseasementioning
confidence: 99%
“…30,31 In one study, the use of nonselective NSAIDs was associated with an increased likelihood of bleeding, whereas selective COX2 inhibitors were not. 30 The extent of use of long-term continued factor prophylaxis initiated after multiple joint bleeds and established joint damage, so-called "secondary" prophylaxis, in adults over 45 is unknown; its effectiveness in mitigating hemophilic arthropathy is also unknown. A European survey found that 23% (58 out of 251) of severe hemophiliacs over 50 years of age were on a regimen of regular concentrate administration, 32 but this may not be similar in the United States, given the variation between the United States and some European countries in prophylaxis practice patterns for pediatric hemophilia patients.…”
Section: Joint Diseasementioning
confidence: 99%